Intravenous Laser Blood Irradiation Increases Efficacy of Etanercept in Selected Subtypes of Juvenile Idiopathic Arthritis: An Innovative Clinical Research Approach - Chiran, Dragos Andrei (Hindawi Publishing Corporation, 2013)
This single-blind, placebo-controlled study assesses the efficacy of synergic administration of intravenous laser blood irradiation (ILBI) and etanercept in selected subtypes of juvenile idiopathic arthritis (JIA). Etanercept is a tumor necrosis factor alpha blocking agent with recognized importance in JIA. Laser radiation has immunomodulatory effects in animal and human studies. Fourteen patients (Group I) received ILBI and 9 patients (Group II) received placebo laser. ILBI was performed in addition to ongoing JIA medication, including etanercept. ILBI was administrated in 3 sets of 5 consecutive daily sessions, with a 7-week interval between every set of sessions. Evaluation was performed using ACR (American College of Rheumatology) Pediatric Criteria (ACR Pedi) at study enrollment and at 10 and 20 weeks, respectively. After 10 weeks, 85.7% of the patients in Group I fulfilled Pedi 30 criteria, compared to only 55.6% of the patients in Group II. After 20 weeks, all patients in both groups had a Pedi 30 response. In Group I, 92.8% of the subjects met the Pedi 50 response, compared to only 55.6% in the placebo group. One patient in Group I responded best, fulfilling Pedi 70 criteria. If applied synergistically, ILBI and etanercept would have an increased efficacy in promoting JIA remission.